Axially Decorated SiIV‐phthalocyanines Bearing Mannose‐ or Ammonium‐conjugated Siloxanes: Comparative Bacterial Labeling and Photodynamic Inactivation1, 2. (6th March 2018) - Grüner, Malte C.; Niemann, Silke; Faust, Andreas; Strassert, Cristian A.
Abstract: Herein, we present a comparative study about the photoinactivation of Staphylococcus aureus (Gram‐positive model) and Escherichia coli (Gram‐negative model) employing a neutral and a dicationic axially functionalized Si IV ‐phthalocyanine. Depending on the charge of the siloxane moiety (neutral monosaccharide or cationic ammonium salt), different interactions with the bacteria were observed, and a differential photoinactivation was facilitated. The intensity of the fluorescence labeling correlated with the photoinactivation of the two types of bacteria: While the neutral species only significantly affected the Gram‐positive cells, we observed that the positively charged photosensitizer interacted both with the Gram‐positive and with the Gram‐negative models. The dicationic photosensitizer labeled both models with a characteristic deep‐red fluorescence and photoinactivated both classes of prokaryotes. In general, our study clearly demonstrates that axially ammoniumsiloxane‐functionalized Si(IV) phthalocyaninates constitute excellent photosensitizers due to their weak aggregation in aqueous environments. In particular, we also show that charge‐based targeting with axial ammonium groups leads toward broad‐spectrum Si IV ‐phthalocyanines for photodynamic inactivation of bacteria. Abstract : We present a comparative study about the photoinactivation of Staphylococcus aureus (Gram‐positive model) and Escherichia coli (Gram‐negative model) employing a neutral and a dicationic axially functionalized Si IV ‐phthalocyanine. Depending on the charge of the siloxane moiety (neutral monosaccharide or cationic ammonium salt), different interactions with the bacteria were observed, and a differential photoinactivation was facilitated. The intensity of the fluorescence labeling correlated with the photoinactivation of the two types of bacteria: While the neutral species only significantly affected the Gram‐positive cells, we observed that the positively charged photosensitizer interacted both with the Gram‐positive and with the Gram‐negative models.